Touchstone : - McCarthy, Michael (Cambridge UNiversity Press, 2005)
Touchstone is an innovative new series for adult and young-adult learners of English. It draws on extensive research into the Cambridge International Corpus of North American English - a large database of everyday conversations and texts that shows how people actually use English. At the core of Touchstone is a brand-new syllabus area of conversation management strategies such as how to start and end conversations, how to show interest, and how to ask questions that are not too direct. The result is a groundbreaking course of language and skills development that helps learners communicate naturally and effectively, even at the very beginning levels.